Study bearing capacity of subgrade using combination bamboo grid and stabilized soil - Aazokhi Waruwu; Paulus Dwi Surya Emili Yanto; Rika Deni Susanti; Syukurman Harefa (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2022)
The subgrade of road construction also determines the strength and resistance to loads on it. The subgrade in the field very varies from soft clay to hard soil. The subgrade of soft clay requires soil improvement to increase bearing capacity. This study aims to determine the increase in bearing capacity and modulus of subgrade reaction in stabilized soil with the bamboo grid. The research was conducted through a physical model using a test box. Soft clay is compacted and the above it is replaced with stabilized soil with and without the bamboo grid. The height of stabilized soil varied from 0-15 cm. The results showed that the bearing capacity increased along with the increase in height of stabilized soil. The subgrade of stabilized soil which was given additional reinforcement of bamboo grid was able to increase the value of bearing capacity and modulus of subgrade reaction. A significant increase was obtained in the height of stabilized soil at least equal to the diameter of the test plate.